2019
DOI: 10.1177/0961203319842663
|View full text |Cite
|
Sign up to set email alerts
|

Combination immunosuppressant therapy and lupus nephritis outcome: a hospital-based study

Abstract: Lupus nephritis (LN) is the leading cause of mortality in lupus patients. This study aimed to investigate the treatment outcome and renal histological risk factors of LN in a tertiary referral center. Between 2006 and 2017, a retrospective observational study enrolled 148 biopsy-proven LN patients. After propensity score matching, 75 cases were included for further analysis. The classification and scoring of LN were assessed according to the International Society of Nephrology/Renal Pathology Society. Treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…A more careful study of urine cells for the identification of molecules involved in kidney cell injury [211] can prove useful in monitoring the response to treatment, as the shed cells may provide a window into the events in the kidney tissue itself. Anti-CRP Clinical disease activity and responses to therapy in LN [34,35] Anti-ENO-1 (+) Diagnosis and prediction of LN [37,38,40] AaA (Low) Diagnosis [41] Anti-chromatin Diagnostic/predictive capacity in LN [48] PTEC-binding IgG (+) Clinical disease activity [167] PHACTR4 icx (+) Diagnosis [168] P3H1 icx (+) Diagnosis [168] RGS12 icx (+) Diagnosis [168] PTEC-binding IgG (+) Clinical disease activity [167] IgM (↑) Responses to therapy in LN [169] ANCAs Resistin (↑) Damage [190] CSF-1 (↓) Responses to therapy in LN [191] HNP1-3 (↓) Responses to therapy in LN [192] S100A8/A9 (↑) Responses to therapy in LN [193] S100A12 (↑) Responses to therapy in LN [193] Urine CSF-1 (↑) Histological disease activity [191] Periostin (↑) Damage [206] C9 (+) Prognosis [207] Podocyte foot process width (↓) Prognosis [169] Arteriolar C4d deposition (+) Prognosis [208] Cellular crescents (+) Prognosis [172] Fibrous crescents (+) Prognosis [172] Glomerular C3 deposition (+) Prognosis [212] IFTA (+) (≥25% of the surface cortical area)…”
Section: Discussionmentioning
confidence: 99%
“…A more careful study of urine cells for the identification of molecules involved in kidney cell injury [211] can prove useful in monitoring the response to treatment, as the shed cells may provide a window into the events in the kidney tissue itself. Anti-CRP Clinical disease activity and responses to therapy in LN [34,35] Anti-ENO-1 (+) Diagnosis and prediction of LN [37,38,40] AaA (Low) Diagnosis [41] Anti-chromatin Diagnostic/predictive capacity in LN [48] PTEC-binding IgG (+) Clinical disease activity [167] PHACTR4 icx (+) Diagnosis [168] P3H1 icx (+) Diagnosis [168] RGS12 icx (+) Diagnosis [168] PTEC-binding IgG (+) Clinical disease activity [167] IgM (↑) Responses to therapy in LN [169] ANCAs Resistin (↑) Damage [190] CSF-1 (↓) Responses to therapy in LN [191] HNP1-3 (↓) Responses to therapy in LN [192] S100A8/A9 (↑) Responses to therapy in LN [193] S100A12 (↑) Responses to therapy in LN [193] Urine CSF-1 (↑) Histological disease activity [191] Periostin (↑) Damage [206] C9 (+) Prognosis [207] Podocyte foot process width (↓) Prognosis [169] Arteriolar C4d deposition (+) Prognosis [208] Cellular crescents (+) Prognosis [172] Fibrous crescents (+) Prognosis [172] Glomerular C3 deposition (+) Prognosis [212] IFTA (+) (≥25% of the surface cortical area)…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, renal survival and patient survival were not assessed in this study. A recent study indicated that activity scores in LN histology were associated with end-stage renal disease [41]. Whether the degree of renal gallium uptake has a predicting role on renal survival in LN patients needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…In research by Chen et al (2019), research was conducted on 149 patients who were separated into 4 groups based on the induction therapy given. Patients received systemic glucocorticoids and immunosuppressants with cyclosporine (50-100 mg/day) or azathioprine (25-50 mg/day) in combination with MPA in the so-called MPAcombination group.…”
Section: The Interaction Betweenmentioning
confidence: 99%
“…However, in this study, hematuria and urine analysis were not measured so this study could not measure the clinical manifestations of the SLEDAI score. In addition, the samples obtained were only small and the SLEDAI score used to measure the success of therapy was the median SLEDAI score, not the SLEDAI score for each patient (Chen et al, 2019).…”
Section: The Interaction Betweenmentioning
confidence: 99%